Influence Analysis of Shielding Gas Flow Rate and Purity Level Variation on GMAW Welding Process to Microstructure of Alumunium 5083 - Nur Syahroni; Sadewa Sechan Winando; Yeyes Mulyadi (International Journal of Offshore and Coastal Engineering (IJOCE), 2021)
Aluminium is a commonly used material in construction and transportation industries. The advantages of using the aluminium material are its light weight, corrosion resistant, and the capability to form an alloy with another metal. Therefore, the aim of this research is to analyze the influence of shielding gas flow rate and purity level variation to mechanical properties and microstructure of the welded material. The welding process used on this research was the GMAW method. The material used was aluminium 5083 series with 300 mm x 150 mm x 8 mm dimensions. The shielding gases used were high purity (HP) and ultra-high purity (UHP) argon (Ar). The variations of shielding gas flow rate used were 16, 18, dan 20 litre/minutes. Based on the tensile test that has been done, the variation of UHP argon gas with 20 litre/minute flow rate had the best result with yield strength of 217,32 MPa and ultimate strength of 295,83 MPa. The result of the micro photos showed that the GMAW method produced small dots where the dots were Mg2Si formation, which the greater number of smaller size dot produced would increase the mechanical properties of  the material.